Antibacterial activity of Streptomyces spp. crude extract on multidrug resistant Psedomonas aeruginosa isolated from clinical samples - Zainab Hasan Abed; Eman Mohammad Jarallah (Medical Journal of Babylon)
Abstract Background: Actinomycetes are the heterogeneous group of microorganisms, which have thread-like filaments, isolated from the soil. Objectives: Isolation, identification, and partial purification of crude bioactive agents of the Actinomycetes isolates and isolation and identification of Pseudomonas aeruginosa from clinical samples, and to study antibiotics susceptibility for these isolates. Materials and Methods: Forty soil samples were collected from different agriculture locations in Hilla city. Soil samples were air dried and pre-treated with calcium carbonate (1%). The best selective medium for growth Actinomycetes is yeast malt extract agar medium (International Streptomyces project—ISP2) with 1 mg/mL Nystatin as antifungal agent. Results: A total of 68 actinomycetes species were isolated and 23 Streptomyces spp. isolates were recovered after molecular identification. By cross- streaking method , the antibacterial activity for these isolated were tested against 30 clinical isolates of P. aeruginosa that showed resistance to 17 antibiotic types of streptomyces isolates demonstrated potential antibacterial activity were mass cultured and secondary metabolites were extracted using ethyl acetate. Among the 23 isolated strains, seven isolates (St4, St5, St6, St8, St11, St12, and St14) demonstrated a significant antibacterial activity with the zone of inhibition ranging from 0 to 22 mm against P. aeruginosa, according to the primary and secondary screening. Conclusion: The isolates St6 and St12 showed the higher antimicrobial metabolites activity, so these isolates were elected for sequencing.